Domestic employment effects of offshoring: Empirical evidence from Finland - Matthias Deschryvere; Annu Kotiranta (The Research Institute of the Finnish Economy (ETLA), 2008)
This study empirically explores whether the propensity to offshore affects the total domestic employment at the firm level. The analysis is based on a Finnish weighted sample of 652 firms and screens the effect of offshoring different kinds of tasks. Two main channels of offshoring tasks are taken into account: offshore outsourcing and in-house offshoring. The main conclusion is that offshoring can significantly affect the total domestic employment but that the significance and the direction of the effect depend on which kind of offshoring is involved. Our results offer evidence that in both the manufacturing and service sectors offshore outsourcing of services has a positive effect on employment. In addition it was found that the effect of R&D offshoring on the probability to anticipate an increase of total domestic employment depends on the offshoring channel. Offshore outsourcing of R&D has a positive effect on the anticipated domestic employment, whereas in-house offshoring of R&D has a negative effect. Specific for the manufacturing sector is that offshore outsourcing of production also has a negative significant effect. A final conclusion is that only in the service sector does in-house offshoring of services have a negative effect on the probability to anticipate an increase of domestic employment. By dissecting offshoring by tasks and channels the above empirical findings contribute to a better understanding of the aggregate effects of offshoring on domestic employment.
Keywords: F16; F23; L20; 330; Globalization; internationalization; outsourcing; offshoring; job loss; domestic effects; home country effects; Offshoring; Auslandsproduktion; Beschäftigungseffekt; Verarbeitendes Gewerbe; Dienstleistungssektor; Betriebliche Forschung; Finnland